Efficacy analysis of the length of entrance on the diffraction of waves behind two breakwaters - Ghadimi, Parviz; Heyvedi, Zahra; Feizi Chekab, Mohammad A. (International Journal of Scientific World, 2015)
Any harbor should be protected from incoming waves. However, these waves are always diffracted at the entrance of the harbor and a fraction of the waves enters the harbor area. In the present paper, by the use of Boussinesq equations solved by Mike21 numerical software, a parametric study on the length of entrance of a simple harbor has been conducted and the diffraction of waves after passing the harbor entrance has been analyzed. As a result, the effects of the length of the entrance have been investigated on the safe zone behind the breakwaters of the harbor. To this end, a parameter called angle of safety is defined as a representative of the safe zone. Finally, an equation is presented to describe the behavior of the safe zone with respect to the length of the entrance. It has been observed that the angle of safety has a minimum of 57.5 degrees which increases with respect to the length of entrance which consequently increases the safe area behind the breakwaters.